Tinjauan Yuridis Pengadaan Tanah bagi Pembangunan Fly Over Jombor Kabupaten Sleman untuk Kepentingan Umum - Abdul Qodir Jaelani dan Purnawanti (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2016)
This paper discusses about mechanism of land supplying for building Jombor fly over in Sleman regency Yogyakarta which is less than 1 (one) hectare. It is only 19 areas. The execution process of land supplying was considered as injustice because of its compensation. In order to resolve this problem, the Government have made mediation programs. They discussed with society trhough Indonesian Ombudsman and the District Legislative especially commission of C. This researche is analysed by using critical legal studies theory and legal system theory with field research decimeter method which uses empiric yuridic approach. It means to see directly the facts in the field in order to describe that the mechanism of land supplying in accordance to Indonesian regulations. in fact, the mechanism of Jombor fly over supplying and building was according to the Indonesian regulations, but it is still unclear and overlapping between one regulation with others.